SilicH2O: a graphical user interface for processing silicate glass Raman spectra and quantifying H2O - van Gerve, Thomas Daniel; Namur, Olivier (Volcanica, 2023)
H2O contents of magmas strongly impact the explosivity of volcanic eruptions, as well as their rheological properties and crystallisation behaviour. Accurate analyses of H2O in magmatic liquids are therefore vital for our understanding of the dynamics of magmatic processes and eruptions. Raman spectroscopy provides an accessible, affordable and high spatial resolution technique for estimating H2O contents of magmas that have been quenched to a glass during eruption. However, calculating H2O concentrations from Raman spectra involves manual data processing and results are therefore sensitive to the specific treatment used. SilicH2O is an open-source software program that uniformises and streamlines this process by providing an interactive graphical user-interface. It can be used to: (a) process Raman spectra of silicate glasses, (b) remove any unwanted peaks through interpolation and unmixing, (c) set up H2O calibrations with reference materials and (d) quantify H2O contents of unknown samples.